2003
DOI: 10.1152/ajpgi.00402.2002
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of intestinal protein synthesis and protease mRNA by luminal and systemic nutrients

Abstract: Route of nutrient supply is important in regulation of intestinal protein metabolism, because total parenteral nutrition, compared with enteral feeding, leads to profound atrophy. Participation of the fractional rate of protein synthesis (Ks), their degradation in regulation of gut protein balance, and their possible modulation by specific nutrients are the focus of our work. We developed an in situ experimental system that allows controlled exposure of intestinal mucosa to nutrients systemically, luminally, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 29 publications
1
21
1
3
Order By: Relevance
“…These data are in agreement with those of other studies demonstrating that luminal nutrients are necessary for stimulating hormonal and/or neural regulation of digestive tissue maintenance and protein synthesis (1,4,11,15,19). The saline-infused orally fed group, which served as a surgical control, accumulated weight over the 7-day experiment; however, this was not to the extent of the nonsurgical control group.…”
Section: Discussionsupporting
confidence: 93%
“…These data are in agreement with those of other studies demonstrating that luminal nutrients are necessary for stimulating hormonal and/or neural regulation of digestive tissue maintenance and protein synthesis (1,4,11,15,19). The saline-infused orally fed group, which served as a surgical control, accumulated weight over the 7-day experiment; however, this was not to the extent of the nonsurgical control group.…”
Section: Discussionsupporting
confidence: 93%
“…This may be related to the fact that, at a similar protein to energy ratio, increasing fat content of the diet strongly stimulates protein synthesis in portal-drained viscera [67]. By contrast, recent data reported that AA provided luminally are a key factor required to reduce the expression of genes connected with intestinal proteolysis [1]. Mucosal protein synthesis can be increased by adding a colostrum extract to the diet [47].…”
Section: Weaning and Protein And Amino Acid Metabolismmentioning
confidence: 99%
“…40,43 Parenteral effects of amino acids on protein synthesis are less clear and may depend on technique, site, or species. Thus, amino acid infusion increased intestinal protein synthesis in dogs 44 but not in pigs 36,45 or human duodenum. 46 Considering our rigid study design (triple mucosal biopsies in the same subjects before and during amino acid infusion), our findings strongly support the idea that a potential anabolic effect of an increased basolateral amino acid supply at the gut does not imply a rise in intestinal protein synthesis.…”
Section: July-august 2005mentioning
confidence: 87%
“…33,34 However, this use does not necessarily reflect enhanced protein synthesis because decreased protein breakdown or accelerated amino acid oxidation is possible. With respect to protein synthesis, enteral protein feeding was without relevant effect in the jejunum of adult pigs, [35][36][37] or in the duodenum of adult man. 38 In contrast to whole proteins, enteral application of free amino acids seems to be more effective, although large amounts may be required.…”
Section: July-august 2005mentioning
confidence: 88%
See 1 more Smart Citation